Verses of Ghadir: a search regarding the Holy Prophet's sermons on the Farewell Hajj and an exegesis of the Qur'anic verses indicating the incident of Ghadir Khumm - VERSES... (Ansariyan Publications, 2003)
why, c.1/dw, c.2